Processos de comunicação na mídia política: os comportamentos comunicacionais no cenário das campanhas eleitorais veiculadas no sistema televisivo reconciliação com a natureza - - Teixeira, Tatiana Gianordoli (2008)
This thesis is dedicated to investigate the source of electoral behavior, one being rational, logical and ideological and the other manifested mainly in the television, toward the seduction of the voter rather than his honest belief. To explain how such behavior, which sometimes seem to escape of what we call rationality, this research argues that elections are rather than be an area of dispute by ideas is a space of actors, working on the basis of a series manipulation tactics aiming the power and domination. We, therefore, have as problem the question: What is the origin of the nature of the speeches used in political campaigns and the communicational efficacy of them? As hypothesis, we propose: the strategies adopted by politicians during the election period, and aspects about the election campaigns carried on television, can be understood in its fundaments from existing information about animal behavior, studied in Ethology - the biology of behavior and the Biosemiotic, in order to understand the specific features of the electoral moment and its relation to our evolution history. We point out that the proposed hypothesis is not reductionist (in the sense to propose only biological explanations) but tries to capture the evolutional complexity contained in the transition from the biological to the psychosocial. The political discourse in the Free Advertising Electoral Period offers a broad field of investigation due to its language to an elaborate work of marketing or conviction. The bridges between the searched authors and our natural context wanted to consider the connection between electoral campaign and animal nature. Within the Program in Communication and Semiotics, this study, combining the social and biological areas, is based on Darwinian evolutionary theory and science of communication, in order to be inserted in the research line of Culture and Media Environment. This thesis took theoretical and practical methodology to test its hypothesis, revealing that the understanding of communication processes of political campaigns, is based on inheritance ethological typical of higher primates. This is because the most primitive component of human beings, the ethological origin, considers the views and strategies of domination in ethological niche occupied by politicians, related to the limbic complex, common to all mammals, rather than the neocortical behavior assigned exclusively to the human species. In the discussions, found the communication processes in political media and the explicit communication behavior, in the figure of candidates as well as the implicit ones, belonging to the agents of political marketing